The evaluation of coated granules to mask the bitter taste of dihydroartemisinin (Brazilian Journal of Pharmaceutical Sciences, 2011)
The purpose of this study was to mask the bitter taste imparted by dihydroartemisinin (DHA) by the use of different coating materials. Trial-1 and trial-2 were conducted to prepare the DHA granules. The granules produced from trial-1 were irregular in shape and smaller in size while the trial-2 granules were more regular and larger in size. The granules obtained from both trials were then coated with two different coating methods, namely A and B, depending upon coating material. The trial-2 granules showed better flow properties than trial-1 granules. In vitro dissolution studies in phosphate buffer at pH 6.8 revealed that granules of trial-2B released only 34% ± 3 DHA in two minutes compared with trial-1A (57% ± 2), trial-1B (48% ± 2) and trial-2A (53% ± 7). The pleasant taste perception (PTP) test also confirmed the taste masking efficacy of trial-2B (P < 0.05). Scanning electron microscopy (SEM) revealed the more regular and smooth surface of trial-2B granules. In addition, the differential thermal and thermogravimetric analysis (TG-DTA) confirmed no interaction between the materials and pure DHA. DHA has shown its characteristic peaks in the x-ray diffraction (XRD) patterns which were also prominent in all the granules. In conclusion, the granules obtained from trial-2B displayed considerable decrease in the bitter taste of DHA thereby fulfilling the purpose of this study.